Efficient Medium Access Control Protocols for Broadband Wireless Communications - Nakpeerayuth, Suvit; Wuttisittikulkij, Lunchakorn; Vanichchanunt, Pisit; Srichavengsup, Warakorn; Wattanamongkhol, Norrarat; Annur, Robithoh; Saadi, Muhammad; Wannakong, Kamalas; Siwamogsatham, Siwaruk (IntechOpen, 2011)
None